التراتب الحجمي للمراكز الحضرية في قضاء رانية للفترة2002 - 2020 - حسين, بيان علي (Sulaimani Journal for Humanities, 2023)
In this study, we shed light on the size ranks of the urban centers in Rania district, which is one of the districts of Sulaymaniyah governorate. This study deals with the future of size ranks of urban centers in the district, according to the target year which is the year 2040, and there are (5) urban centers in the district in 2020, and most of the urban centers are of the small or medium size category, and the researcher used the descriptive and analytical approach, through Data collection and analysis, and through work steps and when applying the (Zipf) theory, we concluded that there is no correspondence between the ideal size according to theory and the real size according to the data of the years 2002 and 2020, and despite the absence of the dominant city in the district, the city of Rania accounted for a percentage of 44% of the total urban population in 2002 and 43.6% in 2020, and when applying the urban balance index, it became clear to us that there is an imbalance or imbalance in the urban system in the district, and one of the most important steps The strategy used to address and improve the population conditions in the district is to follow a population policy with the aim of achieving a balance between the urban and rural population on the one hand, and on the other hand, achieving a balance between the population of urban centers in order to reduce the gap between the size of the population of urban centers.
Keywords: Urban Growth; urbanization rate; Urban System; RankSize Rule; Urban Equilibrium Index